Efficient Market Hypothesis And Stock Market Anomalies: Empirical Evidence In Four European Countries - Rossi, Matteo; Gunardi, Ardi (Journal of Applied Business Research, 2017)
The stock market efficiency is the idea that equity prices of listed companies reveal all the data regarding the company value (Fama, 1965). In this way, there isn’t possible to make additional returns. However, evidence against the Efficient Market Hypothesis is growing. Researchers studied Calendar Anomalies (CAs) that characterised financial markets. These CAs contradict the efficient hypothesis. This research studies some of the most important market anomalies in France, Germany, Italy and Spain stock exchange indexes in the first decade of new millennium (2001- 2010). In this study, to verify the distribution of the returns and their auto correlation, we use statistical methods: the GARCH model and the OLS regression. The analysis doesn’t show strong proof of comprehensive Calendar Anomalies. Some of these effects are country-specific. Furthermore, these country-anomalies are instable in the first decade of new millennium, and this result demonstrates some doubt on the significance of CAs.
Keywords: EMH; Calendar Anomalies; January Effect; Weekdays Effect; France; Germany; Italy; Spain